Analysis of cell-mediated immune responses in support of dengue vaccine development efforts. Issue 50 (10th December 2015) - Rothman, Alan L.; Currier, Jeffrey R.; Friberg, Heather L.; Mathew, Anuja
Abstract: Dengue vaccine development has made significant strides, but a better understanding of how vaccine-induced immune responses correlate with vaccine efficacy can greatly accelerate development, testing, and deployment as well as ameliorate potential risks and safety concerns. Advances in basic immunology knowledge and techniques have already improved our understanding of cell-mediated immunity of natural dengue virus infection and vaccination. We conclude that the evidence base is adequate to argue for inclusion of assessments of cell-mediated immunity as part of clinical trials of dengue vaccines, although further research to identify useful correlates of protective immunity is needed.